UPAYA MENINGKATKAN KEMAMPUAN PRAMEMBACA PADA ANAK USIA 4–5 TAHUN MENGGUNAKAN MEDIA PERMAINAN KARTU DI SPS DAHLIA 79 - Widianti Primasari; Ianatuz Zahro; Trio Suwargono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pre-reading skills are the initial skills in recognizing letter symbols, understanding the relationship between sounds and letters, and building a foundation for literacy before children learn to read formally. Introducing reading for early childhood requires a fun and engaging method to understand the letters, numbers, or symbols being presented. An educator can use many methods to develop aspects of early childhood language development so that children do not get bored easily. Based on initial observations conducted by researchers at SPS Dahlia 79 Kalisat-Jember, some children still have difficulty recognizing the alphabet and numbers, distinguishing initial sounds, and are less interested in activities related to reading. This phenomenon emerged during the learning process in class, where when the teacher sang the alphabet symbols "ABCDEFG", students were interested in following until the end of the song. However, when the teacher sequenced the letters manually (without using songs or notes), what happened was that students felt confused by the symbols rather than the alphabet itself. Teachers in early childhood education, especially at SPS Dahlia 79 Kalisat-Jember, need to use a fun and character-appropriate approach to develop pre-reading skills indirectly and naturally. Teachers in PAUD, especially at SPS Dahlia 79 Kalisat-Jember, need to use a fun and character-appropriate approach to develop pre-reading skills indirectly and naturally. This research is a Classroom Action Research (CAR) where according to classroom action research it can be defined as a form of scientific and methodical study or activity carried out by teachers/researchers in the classroom using actions to improve the learning process and outcomes. The population in this study were Early Childhood (both boys and girls) at SPS Dahlia 79 in Kalisat District. Data were analyzed descriptively qualitatively and quantitatively (percentage of completion per cycle). In cycle I, the achievement of pre-reading skills of children aged 4–5 years at SPS Dahlia 79 was still limited: only 27% (4 out of 15) children were in the Very Well Developing category, the rest were in Developing According to Expectations (20%), Starting to Develop (47%), and Not Yet Developing (7%). Children generally cannot name 10 letters correctly, matching letters to pictures, and constructing simple syllables independently. Obstacles identified included low media interest, minimal active practice, and a lack of individual support. Meanwhile, in cycle II, results showed that 80% of children (12) achieved the Very Good Development category and 20% achieved Development as Expected, with none in the bottom two categories. Children were more confident, active, and able to name letters, match them to pictures, and construct syllables such as "IBU," "UBI," and "ABI" independently.